2018
DOI: 10.1111/cen.13799
|View full text |Cite
|
Sign up to set email alerts
|

Cushing's disease in older patients: Presentation and outcome

Abstract: Older patients with CD appear to have a distinct phenotype with a more catabolic picture, including a lower BMI and greater prevalence of muscle wasting. Surgical outcomes are similar without a significant age-related increase in complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
1
13
1
Order By: Relevance
“…Our data also showed that aging attenuates the well-known female preponderance in the prevalence of PIT-CS observed in adult population (14,16). In fact, slightly more than half of the elderly patients were females, whereas women represented almost three-quarters of the younger patients.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our data also showed that aging attenuates the well-known female preponderance in the prevalence of PIT-CS observed in adult population (14,16). In fact, slightly more than half of the elderly patients were females, whereas women represented almost three-quarters of the younger patients.…”
Section: Discussionsupporting
confidence: 74%
“…Conversely, in a recent study, Qiao et al showed that 45 CD patients older than 60 more commonly presented with a catabolic phenotype and cardiometabolic comorbidities as compared with younger patients (14).…”
Section: Significance Statementmentioning
confidence: 89%
“…Older patients with CD appear to have a distinct phenotype with a highly catabolic nature, including lower BMI and greater prevalence of muscle wasting [52]. A number of comorbidities tend to be more common in older patients than in younger patients, including hypertension, diabetes mellitus, history of cardiovascular disease, and history of deep vein thrombosis.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…On the contrary, in a study by Qiao at al. including 45 patients with CD older than 60 years and 90 patients below this age, no age-related differences in adenoma size were reported [10]. Aging appears to also attenuate the typical female preponderance in the prevalence of pituitary CS, in that slightly more than a half of the elderly patients were females in the ERCUSYN population, whereas women represented almost three-quarters of the younger patients [9].…”
mentioning
confidence: 92%